Enforcement of Criminal Law on Crimes of Criminal Consensus Against State Security: Learning from Indonesia - Roby Satya Nugraha; Sri Ayu Astuti (Rechtsidee, 2020)
The purpose of this legal research is to explain the first discussion, namely how to implement law enforcement against criminal conspiracy (samenspanning) which has been regulated in the Criminal Code and the Criminal Procedure Code. Second How is the imposition of sanctions for criminal conspiracy charges regulated in the Criminal Code in case Number: 293K / Pid / 2016. This type of research is normative research which is descriptive-analytical in nature, using secondary data with data collection techniques through library research and processing data qualitatively, it is concluded that law enforcement against criminal conspiracy is carried out by penal measures, penal measures are one of the efforts to enforce the law or all actions taken by law enforcement officials that focus more on eradication after a crime is committed under criminal law, namely criminal sanctions which constitute a threat to the perpetrator. The stages in this way include investigation, further investigation, prosecution, and so on, which in this case is part of criminal politics. The functionalization of criminal law is an effort to tackle crime through rational criminal law enforcement with the aim of creating the fulfillment of a sense of justice and efficiency. The imposition of sanctions Criminal sanctions imposed if a person has been proven to have committed a criminal act of treason can be punished with a criminal sentence contained in Article 106 of the Criminal Code with the threat of life imprisonment or twenty years in prison.